PENGARUH PENERAPAN STRATEGI PEMBELAJARAN FIRE UP TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI MTS ROUDLOTUL ULUM KECAMATAN TANDUN KABUPATEN ROKAN HULU - Aswan Nur Hamzah; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of the FIRE UP learning strategy on student learning activeness in the eyes of PPKn in MTs Roudlotul Ulum, Tandun District, Rokan Hulu Regency. The formulation of the problem in this study is whether the use of the FIRE UP learning strategy affects student learning activeness in PPKn subjects in Roudlotul Ulum MTs, Tandun District, Rokan Hulu District. This research uses an experimental qualitative approach. The population in this study was grade VII students at Roudlotul Ulum MTs in Rokan Hulu district. The sample in this study was taken based on the "Random Sampling" technique. Where classes taken as samples are students of class VII A (experimental class) who are given a learning strategy FIRE UP and class VII B (control class) are students who are given the conventional method. Then the data analysis using homogeneity test, t-test and gain test. Based on the results of the study showed that there is an effect of learning activeness between students who use the conventional FIRE UP learning strategy at Roudlotul Ulum MTs in Rokan Hulu district can be seen from the results (Tcount = 23.38> Ttable = 2.018). Where there is an increase in the average activity of learning in the experimental class PPKn from 67.41 to 70.36 and the average activity of learning in the control class PPKn from 59.56 to 61.08. With an average gain of 0.28 included in the category of "low" Thus there is an influence on the activity of student learning in PPKn subjects by applying the FIRE UP learning strategies conventionally in Roudlotul Ulum MTs in Rokan Hulu district.Key Words: Influence, FIRE UP, Activity